A high school supercomputing challenge - Cohen, Marion; Foster, Marilyn; Kratzer, David; Malone, Patricia; Solem, Ann (Proceedings of the 1991 ACM/IEEE Conference on Supercomputing, 1991)
The national need for scientists and engineers and for a public that understands science and technology is more urgent today than ever before if the United States is to maintain its productivity and technical edge in the world market. Many capable high school students, however, lose interest in pursuing scientific academic subjects and in considering science or engineering as a possible career. An academic program that progresses from a statewide to a national competition is a way of developing science and computing knowledge among high school students and teachers, as well as instilling enthusiasm for science. This paper describes the New Mexico High School Supercomputing Challenge, a nonselective academic-year long program that was initiated in 1990. Teams of high school students from throughout New Mexico do a team computational science project using high-performance computers.